Limpopo River Basin digital twin: enabling sustainable water management with the open data cube framework - Afham, Abdul; Kiala, Zolo; Ghosh, Surajit (2025)
The Limpopo River Basin Digital Twin is a data-driven platform designed to support sustainable water management across the transboundary Limpopo River Basin, which faces increasing pressures from climate variability and competing water demands. At its core is a dynamic catalog of Earth observation raster datasets, structured and indexed using the Open Data Cube (ODC) framework. This infrastructure enables efficient curation, discovery, and integration of spatial-temporal data critical to basin-scale monitoring and planning.